The use of 3D ultrasound for the prediction of success of vaginal birth prior to instrumental delivery. (7th June 2011) - Agarwal, U; Bricker, L; Alfirevic, Z
Abstract : Introduction: Digital examination in second stage of labour to assess fetal head station and rotation is often inaccurate and poorly reproducible. Recent evidence suggests that translabial ultrasound in 2nd stage of labour allows more accurate assessment and may be a better predictor of successful vaginal birth. Aims: To evaluate the predictive value of four parameters obtained from 'SonoVCAD labor' GE software (head direction, midline angle, progression distance, angle of progression) when applied to women in prolonged second stage of labour in whom decision has been made to perform instrumental delivery (forceps, ventouse). Methods: We analysed 3D volumes from 17 women immediately before attempting instrumental delivery in theatre. 12 women were delivered with Kjellands forceps, 1 with ventouse and 1 with Simpson's forceps. Three caesarean sections (CS) were performed after failed forceps. We related head direction angle (>95°), midline angle (<45°), progression distance (>6 cm) and angle of progression (>160°) with the success or failure to achieve vaginal birth. Results: Head direction angle >95° predicted 100% cases of successful instrumental delivery. Whereas an angle of progression of >120° predicted 86% of all successful instrumental deliveries. Midline angle and progression distance were not found to be good predictors of instrumental delivery. Conclusions: Head direction angle >95° and angle of progression >160° appear to be good predictors of successful instrumental delivery while midline angle and progression distance are unlikely to be useful in this clinical scenario. An intervention study is needed to confirm the feasibility and effectiveness of these parameters when used for clinical decision making in real time.